Karakteristik komite audit dan kinerja bank: Komparasi syariah dan konvensional - Katsirin, Khairul; Syarief, Moch. Edman; Sumiyati, Sumiyati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study intends to analyze the effect of the characteristics of the Audit Committee on the performance of Islamic and conventional comparative banks in Indonesia. This study uses a quantitative approach with comparative methods and Partial analysis of Least Square-Structural Equation Model. The independent variables used include size, women's involvement, financial expertise, independence and number of meetings, while the dependent variable uses return on assets as a projection of bank performance. Data for all variables are obtained from annual reports that have been published on the official website of each bank. The results of the study found that the involvement of women and financial expertise had an effect on the performance of Islamic banks and independence and the number of meetings had an effect on the performance of conventional banks.